Cost estimation and consumer acceptance studies of herbal burfi - Prasad, Writdhama G; Khamrui, Kaushik; Rathod, Gunvantsinh; Gupta, Hari Ram (Indian Journal of Dairy Science, 2019)
Traditional Indian dairy product has huge liking throughout the length and breadth of our country as well as abroad in the Indian diaspora. However, increasing health consciousness among the consumers has resulted into shift in their demand to functional foods. Many reports have highlighted the scope of further enhancing traditional dairy foods market by increasing their functionality, however very limited literature is available regarding their market prospects. The present study was conducted to estimate the production cost of herbal burfi, rich in anti-oxidative activity, in comparison to control burfi and also the market potential of the same. Herbal essential oil incorporation resulted into increase in INR 6/- of the raw material cost and thus the production cost of herbal burfi was INR 6/- (2.75%) was higher than that from control burfi. Consumer survey of the developed product revealed that 22.73% of the respondents rated the product ‘excellent’ and 92.86% of 154 respondents were ready to purchase the product, when available in market even at slightly higher price.